Design and Operational Performance of Needlefish Gillnets along the Coast of Ramanathapuram District, Southeast Coast of Tamil Nadu - M. Ilaiyaraja; N. Neethiselvan; B. Sundaramoorthy; B. Ahilan; T. Ravikumar; Kalaiarasan Muthupandi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study undertaken to analyse the design and operational aspects of Needlefish gillnets of four different fishing villages of Ramanathapuram district of Tamilnadu, revealed the existence of notable difference with respect to catch rate despite having many common design features. Relatively shallow and broader continental shelf boarded with coral reef was found to serve as an ideal habitat for Needlefishes along the coastal villages of this district. Six species viz.,Ablenneshians, Tylosurus crocodiles, T. choram, T. agus,Strongylura strongylura and S. leiura were found to constitute the fishery of Needlefish in gill nets with the dominant species being either A. hians orT. crocodiles.A. hians was dominant in the gillnet catches Gulf of Mannar while T. crocodiles showed its dominance in the gillnet catches from the fishing villages of Palk bay. Trawling was found to be a common disturbing activity for Needlefish gillnetting in all the four fishing villages studied. Among four villages, Mundal was found to be notable for Needlefish gillnetting as relatively longer gill nets involving more number of fishing crafts were found to be operated from this village. The catch composition of gillnets revealed that the mean Catch Per Unit Effort (CPUE) of Needlefishes ranged from 23 to 25 nos/boat/day while the CPUE of commercially important fishes such as seer fish, barracudas, mackerels, flying fish, queen fish and sail fishes altogether ranged from 15 to 19 nos/boat/day. The study suggests evolving a selective pelagic longline gear for capturing Needlefishes considering the rich resource of Needlefish along the coast of Ramanathapuram district of Tamil Nadu.